2016
DOI: 10.1016/j.radonc.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

SPACE – A randomized study of SBRT vs conventional fractionated radiotherapy in medically inoperable stage I NSCLC

Abstract: There was no difference in PFS and OS between SBRT and conventionally treated patients despite an imbalance of prognostic factors. We observed a tendency of an improved disease control rate in the SBRT group and they experienced better HRQL and less toxicity. SBRT is convenient for patients and should be considered standard treatment for patients with inoperable stage I NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(196 citation statements)
references
References 31 publications
6
185
0
5
Order By: Relevance
“…No difference in local control was discovered. 26 They found that conventional treatment was associated with a higher risk of grade 1-2 toxicity (oesophagitis and pneumonitis) and with worse treatment compliance; in addition, the SABR group may have had more unfavourable prognosticating factors (T 2 tumours 47% vs 25%; male 45% vs 36%). The Trans Tasman Radiation Oncology Group (TROG) CHISEL Phase III trial comparing SABR to conventional RT is currently recruiting patients and is close to completing recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…No difference in local control was discovered. 26 They found that conventional treatment was associated with a higher risk of grade 1-2 toxicity (oesophagitis and pneumonitis) and with worse treatment compliance; in addition, the SABR group may have had more unfavourable prognosticating factors (T 2 tumours 47% vs 25%; male 45% vs 36%). The Trans Tasman Radiation Oncology Group (TROG) CHISEL Phase III trial comparing SABR to conventional RT is currently recruiting patients and is close to completing recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…This latter trial enrolled 102 patients with T1-2 NSCLC and randomized them to SBRT (66 Gy in 3 fractions in 1 week) using a 5-10 mm expansion for uncertainty vs. CRT (70 Gy in 35 Gy over 7 weeks) using a 20 mm expansion. The results, recently reported in abstract form, 37 suggested a tendency toward improved disease control at 3 years with SBRT, with similar OS between the two arms, and less toxicity with SBRT. 37 Full results of this trial, along with data from the two ongoing randomized trials, are awaited.…”
Section: Randomized Comparisons Of Sbrt With Other Treatmentsmentioning
confidence: 67%
“…The results, recently reported in abstract form, 37 suggested a tendency toward improved disease control at 3 years with SBRT, with similar OS between the two arms, and less toxicity with SBRT. 37 Full results of this trial, along with data from the two ongoing randomized trials, are awaited.…”
Section: Randomized Comparisons Of Sbrt With Other Treatmentsmentioning
confidence: 67%
“…No differences in OS and PFS were observed, though patients treated with SBRT reported better quality of life and less toxicity 78 .…”
Section: Barcelona Respiratory Networkmentioning
confidence: 86%